Trap-Controlled White Electroluminescence From a Single Red-Emitting Thermally Activated Delayed Fluorescence Polymer - Yang, Yun; Yang, Liuqing; Li, Xuefei; Zhao, Lei; Wang, Shumeng; Ding, Junqiao; Wang, Lixiang (Frontiers in Chemistry, 2020)
Single white-emitting polymers have been reported by incorporating the second-generation carbazole dendron into the side chain of a red-emitting thermally activated delayed fluorescence (TADF) polymer. Due to the prevented hole trap effect, in this case, excitons can be generated simultaneously on the polymeric host and the red TADF dopant to give a dual emission. Consequently, a bright white electroluminescence is achieved even at a dopant loading as high as 5 mol.%, revealing a maximum luminous efficiency of 16.1 cd/A (12.0 lm/W, 8.2%) and Commission Internationale de l’Eclairage (CIE) coordinates of (0.42, 0.32). The results clearly indicate that the delicate tuning of charge trap is a promising strategy to develop efficient single white-emitting polymers, whose low-band-gap chromophore content can be up to a centesimal level.